Lab-scaled performance evaluation of novel water-lean solvents for post combustion CO2 capture - Tanthana, Jak; Mobley, Paul; Rayer, Aravind V.; Gupta, Vijay; Soukri, Mustapha; Lail, Marty (International journal of greenhouse gas control, 2021)
•A 100 hr lab-scale CO2 capture was performed using a water-lean solvent, NAS.•NAS showed lower regeneration energy than aqueous MEA at the same capture rate.•A split CO2-rich stream to the desorber lowers water and solvent vapors in CO2 product.•An organic modifier added to NAS lowers the amine emission. This work focuses on demonstrating the energetic performance and operational reliability in a continuous system of RTI's water-lean solvents for post-combustion CO2 capture applications. RTI's Non-Aqueous Solvent, NAS-1A was subjected to 100 h of continuous, CO2 capture and regeneration operation using a Lab-scale Gas Absorption System (LsGAS) while the CO2 capture efficiency, mass balance, and total energy inputs were monitored. Throughout the test period, NAS-1A demonstrated stable operation with 90% CO2 capture while requiring about 15% lower total energy input for solvent regeneration compared to 30 wt% monoethanolamine (MEA) solution. The use of a slipstream of CO2-rich solvent from the absorber sump reduced the regenerated CO2 temperature before the gas was further cooled by the overhead condenser at the top of the desorber. The rich-split setup combined with a wash section may be an effective approach to remove water and solvent vapor from the regenerated CO2 as well as to recover heat at the top of the desorber. NAS-1B was later developed and included a modifier component that lowers the heat of CO2 absorption and reduces the vapor pressure of the amine component. The total energy inputs for 90% CO2 capture with NAS-1B was found to be 25% less than that of the MEA. A gas chromatograph was used to monitor the amine concentration in the gas leaving the absorber wash section. It was found that under similar operating conditions, the presence of the modifier in NAS-1B reduces the amine in the absorber off-gas from 143 ppm in NAS-1A to 20 ppm.